Evaluation in the (Digital) Humanities: Opportunities and Challenges - Žic Fuchs, Milena (Array, 2013)
The presentation addresses the problem of incorporating research and work in the Digital Humanities as part of evaluation processes for positions and promotions. For this area of research, at present mainly done by early career researchers, evaluation tools have not yet been developed and the area itself is still to be recognized as a lege artis field.